Port-wine stain treatment with 577-nm laser: Treatment outcomes of superficial versus deep lesions - Siskawati, Yulia (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Port-wine stains (PWS), or capillary malformations (CM), are congenital vascular anomalies characterized by gradual enlargement of the superficial cutaneous vascular plexus, leading to low-flow malformations in the skin. Laser therapy remains the preferred treatment for PWS. The 577-nm vascular laser system is particularly suited for treating cutaneous vascular disorders. This study evaluates the efficacy of the 577-nm vascular laser for both superficial and deep PWS lesions. Case Illustration: Three adult patients, all aged over 17 years old, were treated with the 577-nm laser. In the first case with deeper PWS, four treatment sessions resulted in flattening of hypertrophic areas, leaving residual red patches. In the second case, complete clearance of the PWS was achieved after eight treatment sessions. In the third case, additional treatment with the 577-nm laser was administered after a device targeting deeper vascular structures was employed. Discussion: The 577-nm vascular laser is safe for use in dark-skinned patients, with a short downtime and low risk of scarring and post-inflammatory erythema. For lesions deeper than 0.8 mm, other treatment modalities should be considered. Early intervention can help prevent the development of hypertrophic or nodular components. Multiple 577-nm laser sessions can minimize progression and provide significant improvement. Treatment success depends on clinical conditions, appropriate laser parameters, and timing. Conclusion: The 577-nm vascular laser is effective and safe for treating PWS, particularly in dark-skinned individuals. Early intervention and multiple sessions are the key to preventing progression and achieving optimal results. Deeper lesions may require alternative laser modalities.